Expression of New York esophageal squamous cell carcinoma 1 and its association with Foxp3 and indoleamine‐2, 3‐dioxygenase in microenvironment of nonsmall cell lung cancer. (30th April 2019) - Wang, Huishan; Xia, Yuan; Yu, Jiaming; Guan, Hong; Wu, Zhengsheng; Ban, Dongcheng; Wang, Mingjun
Abstract : Lung cancer is one of the most prevalent and fatal cancer worldwide. The traditional treatments including surgery, radiotherapy, chemotherapy and targeted therapy are not satisfactory because of severe side effects and/or relapse. Genetically engineered T‐cell–based immunotherapy for malignant cancer shows promise in recent clinical trials. T‐cell receptor (TCR)‐engineered T cells targeting New York esophageal squamous cell carcinoma 1 (NY‐ESO‐1) have been employed in a number of clinical trials for late stage melanoma, synovial sarcoma, multiple myeloma and other malignancies. Owing to the significant efficacy and controllable side effect, NY‐ESO‐1 has been considered as one of the most ideal TCR‐engineered T cell therapy (TCR‐T) cell target for solid tumors, including nonsmall cell lung cancer (NSCLC). However, the incidence of NY‐ESO‐1 expression and its relationship with immunosuppressive microenvironment of NSCLC are largely unclear. In this study, we analyzed the expression of NY‐ESO‐1 and two key immune regulators, Forkhead box P3 (Foxp3) and indoleamine‐2, 3‐dioxygenase (IDO), in 156 NSCLC specimens by immunohistochemistry. Our results showed that NY‐ESO‐1 positive rate is 28.1% (44/156) and significantly higher in distal metastasis ( P = 0.012) and late stage ( P = 0.019) NSCLC patients. In addition, we found that NY‐ESO‐1 expression was positively associated with Foxp3 level but not IDO. These findings implied the potential role of NY‐ESO‐1 in tumor immune escape of NSCLC and indicated the requirement to remove Treg cells in TCR‐T cell therapy for NSCLC patients.